Robot and working tube-assisted invasion-controlled surgery for spinal metastases - Zhou, Shangbin; Li, Bo; Wang, Pengru; Xu, Meiling; Zhao, Jian; Duan, Shujie; Zhu, Zhipeng; Xu, Wei; Xiao, Jianru (Frontiers in Surgery, 2023)
Objective This study aims to highlight the use of robots in surgery and that of tube-assisted minimally invasive surgery for spinal metastases, as well as elaborate on the concept of invasion-controlled surgery (ICS). Summary of background Many patients with spinal metastasis cancer cannot afford serious complications when undergoing traditional open surgery because of their poor physical condition. Robots and minimally invasive technology have been introduced into the field of spine surgery and they have shown significant advantages. Methods Six patients who underwent robot and working tube-assisted ICS for spinal metastases. Relevant demographic, medical, surgical, and postoperative data were collected from medical records and analyzed. Results Mean operative time was 3.8 h and the mean length of the surgical incision was 4.9 cm. The mean estimated blood loss was 400 ml. The mean bedtime and hospital length of stay were 3.2 days and 6.5 days, respectively. No obvious complications were reported during treatment. The mean accuracy of screw placement was 98%. The mean time for further system treatment after surgery was 5.8 days. All patients experienced significant pain relief. The mean preoperative visual analog scale (VAS) was 7.83 points. The mean VAS at 1 day, 1 week, and 1 month after surgery were 2.83, 1.83, and 1.17 points, respectively. Frankel grade was improved in five of six patients. One patient preoperatively with Frankel grade D was the same postoperatively. Conclusion The concept of ICS is suitable for patients with spinal metastases. Robot and working tube-assisted ICS for spinal metastases is one of the safest and most effective treatment methods.